Variation in the hatching response of Ochlerotatus albifasciatus egg batches (Diptera: Culicidae) in temperate Argentina - Campos, Raúl E. (2006)
Egg hatching of winter-collected Ochlcrotatus albifasciatus was studied for six months. Batches of eggs were divided into two groups, one of them was stored in the laboratory at 23°C and 12:12 photoperiod, and the other in the field under dead leaves. Every month, from July to December, eggs from the two groups were flooded under both laboratory and field conditions. Unhatched eggs were returned to the original condition and flooded two more times separated by ten-day intervals. Results show that egg diapause is expressed in different intensities, not only on eggs exposed to different conditions but also in those exposed to the same condition, even when they were laid by the same female. Successive inundations yielded incomplete hatches of eggs, and favored the hatching response in the next flooding. Low environmental temperatures before and during the flooding depressed hatching response. This shows that eggs need a warm period before flooding as well as warm temperatures during flooding, to hatch. As drought period was longer hatching response increased, but this was also accompanied by warmer environmental conditions. The experiment performed in laboratory did not show that increment. Field studies showed that a layer of dead leaves protected eggs from extreme temperatures.